The Impact of 6Ps Storytelling Technique on EFL Young Learners’ Reading Comprehension and Word Recall - Sudharni; Sutapa Yuliana; Susilawati Endang (Universitas Negeri Semarang, 2026)
This study examined the effects of the 6Ps in storytelling technique (Pique, Present, Plan, Play, Ponder, and Punctuate) on young learners’ reading comprehension and word recall. A quasi-experimental design was conducted with 60 third-grade students at a private school in Pontianak. Two intact classes were assigned as the experimental and control groups using cluster random sampling. The experimental group received instruction through the 6Ps storytelling technique, while the control group was taught using conventional storytelling. Pre-tests and post-tests were administered, and the data were analyzed using Analysis of Covariance (ANCOVA) to control for baseline differences. The findings revealed a statistically significant effect on reading comprehension, that is 71% and word recall, 64%. The experimental group achieved higher scores, indicating the effectiveness in teaching reading comprehension and word recall. Therefore, primary English teachers are suggested to integrate this 6Ps in storytelling to teach reading comprehension and word recall.